Desain Bahan Ajar Bahasa Indonesia Bagi Penutur Asing (BIPA) Bermuatan Budaya Lokal Sumatera Utara Melalui Pendekatan Kualitatif Deskriptif - Khadavi Khadavi; Luci Epita Banjarnahor; Putri Enjel Tarigan; Yemima Rina Yanti Panjaitan; Safinatul Hasanah Harahap (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze BIPA teaching materials by including the local culture of North Sumatra. This research uses a descriptive qualitative approach. Data collection techniques include documentation and data sources from BIPA teaching materials which include the local culture of North Sumatra. The data analysis technique uses the concept of Prastowo theory. The results of this research are BIPA teaching materials with Angkola Batak ethnic culture really help foreign language speakers in understanding Indonesian with the cultural nuances of the Angkola Batak ethnic tribe. This can be seen from the material which is prepared systematically and structured.